2005
DOI: 10.1111/j.1572-0241.2005.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening Colonoscopy in Chinese and Western Patients: A Comparative Study

Abstract: Compared to Westerners, Chinese patients have a slightly lower prevalence of colon neoplasia (but not advanced neoplasia), more distal distribution of neoplasia, and higher likelihood of concomitant proximal advanced neoplasia and distal neoplasia. Colonoscopy is safe, well-tolerated, and a viable screening option in Chinese patients, but its advantage over sigmoidoscopy as a screening tool may be smaller.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 23 publications
5
56
3
Order By: Relevance
“…This is quite a high prevalence when compared with other studies of the Chinese population. In Taiwan, Cheng et al [21] reported an advanced polyps' prevalence of 1.3%, and Soon et al [22] a prevalence of 4.0%. We aimed at investigating the change of distribution and the mean age of onset of colorectal polyps, if any, over the past eight years in a regional hospital.…”
Section: Introductionmentioning
confidence: 99%
“…This is quite a high prevalence when compared with other studies of the Chinese population. In Taiwan, Cheng et al [21] reported an advanced polyps' prevalence of 1.3%, and Soon et al [22] a prevalence of 4.0%. We aimed at investigating the change of distribution and the mean age of onset of colorectal polyps, if any, over the past eight years in a regional hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the sample size of the validation cohort, we made reference to the study by Yeoh et al in Asian countries, which indicated a minimum of 1,800 cases to attain a power of 80% for detection of a risk factor with OR of 2 at an alpha level of 0.05. This is based on the estimated prevalence of advanced neoplasia of 4.5% in other Asian colorectal advanced neoplasia studies 14,33,35 . Development of risk score from the derivation cohort.…”
Section: Methodsmentioning
confidence: 99%
“…20 As the screening cohort did not receive FS, the sensitivity and specificity of FS was assumed to be 75-80 and 60-90%, respectively, according to published literature. 21,22 The population was expected to develop CRC according to the age-specific incidence rates of CRC in Hong Kong 15 in the absence of CRC screening. We made reference to a study conducted in Japan 23 and three landmark randomized controlled trials, [24][25][26] and assumed that FIT could reduce CRC incidence by 33%.…”
Section: Clinical Transition Probabilitiesmentioning
confidence: 99%